2016
DOI: 10.1186/s13054-016-1406-2
|View full text |Cite
|
Sign up to set email alerts
|

Pyrexia: aetiology in the ICU

Abstract: Elevation in core body temperature is one of the most frequently detected abnormal signs in patients admitted to adult ICUs, and is associated with increased mortality in select populations of critically ill patients. The definition of an elevated body temperature varies considerably by population and thermometer, and is commonly defined by a temperature of 38.0 °C or greater. Terms such as hyperthermia, pyrexia, and fever are often used interchangeably. However, strictly speaking hyperthermia refers to the el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 62 publications
1
49
0
6
Order By: Relevance
“…16 Although the term fever is commonly understood, no universally accepted definition exists, and it is often used interchangeably with the terms pyrexia or hyperthermia. 2,17 Similarly, there is no accepted temperature threshold that defines the occurrence of fever, with between 5 and 14 different thresholds reported in various studies identified by a literature review. 2 A threshold of !38.3 C is often cited.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16 Although the term fever is commonly understood, no universally accepted definition exists, and it is often used interchangeably with the terms pyrexia or hyperthermia. 2,17 Similarly, there is no accepted temperature threshold that defines the occurrence of fever, with between 5 and 14 different thresholds reported in various studies identified by a literature review. 2 A threshold of !38.3 C is often cited.…”
Section: Discussionmentioning
confidence: 99%
“…Fever is common in critically ill patients with neurological conditions. 2,3 In those with AIS or TBI, fever can contribute to secondary brain injury, and is associated with poorer functional outcomes and higher morbidity and mortality. 4e6 Fever has an infectious cause in about half of all cases.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…17 Nevertheless the diagnosis of hospital-acquired infections poses quite a challenge in the critically ill patient, as up to 50% of febrile episodes are of noninfectious origin, e.g., in burn patients, trauma patients, and patients with severe pancreatitis. 18 A daring quasi-experimental before and after study suggested that a restrictive antibiotic approach in hemodynamically stable patients might be beneficial with a 50% reduction in adjusted mortality, a shorter duration of therapy, and higher rates of appropriate initial therapy. 19 It should be emphasized that in this study only nonseverely ill patients were included.…”
Section: Sense and Nonsense Of "Watchful Waiting" In Severely Ill Patmentioning
confidence: 99%
“…Una variación de la Tº corporal entre 0.5 y 1ºC, es considerada aceptable y dependiente de la temperatura ambiente que rodea el paciente, no entanto un aumento > de 1ºC, es asociado a mayor estrés fisiológico y a un incremento en la mortalidad del paciente crítico. La disminución de temperatura en el paciente en estado crítico, parece ser protectora hasta 1ºC, y son provocadas por el ambiente externo o por una patología propia del paciente ( neurológica) 67,68,69,70 .…”
Section: Discussionunclassified